East Central European migrations during the Cold War : a handbook - Mazurkiewicz, Anna (De Gruyter reference., 2019)
"An extremely useful and much needed survey. Over eleven chapters, authors from eight countries cover the complex history of migration from the perspective of Central and Eastern Europe between 1945 and 1993. Following in the footsteps of Klaus Bade's Encyclopedia of European Migrations, the authors make extensive use of sources in national languages, while providing an extensive overview of population movements in the region between the Baltic, Black, and Adriatic Seas. The individual chapters shed light on phenomena overlooked in other volumes, including individual state reactions to various migratory phenomenon, and the political, economic, and ideological consequences of human movement. The chapters of this volume are uniform not only in their informative nature, but also in suggesting new pathways for in-depth research." Adam Walaszek, Jagiellonian University, Kraków, Poland "Eastern Europe is an emblematic space of mobility and its Cold War history cannot be told without considering migration from and into the countries of the region. This volume comes at a timely moment and provides a uniquely comprehensive account, full with useful information for further research. It will be a must-read both for migration studies scholars and for area specialists." Ulf Brunnbauer, Leibniz Institute for East and Southeast European Studies, Regensburg, Germany "The Handbook is a gift to students of migration on three counts. It gathers the expertise of scholars fluent in the languages - and familiar with the archives - of Eastern and Central Europe. Thus it brings the multi-layered and complex histories of movement beyond the flat descriptor of "Soviet bloc" or Eastern European migrations. The Handbook is both rich and lucid, presenting in-depth materials on the European twentieth-century, on one hand, and organizing each chapter in a similar way, offering the reader transparently comparable histories. From Estonia south to Albania, and from the USSR west to the GDR, each chapter elucidates a complex migration history distinguished by national politics, ethnic composition, and economics - moving from the cataclysmic impacts of World War II to the international migrations and politics of Cold War movement, as well as the politics of Cold War emigrants themselves. Each chapter ends with an epilogue on post-1989 international migrations and a valuable addendum on published and archival sources. Finally, the Handbook models the kind of high quality work produced by international scholarly cooperation at its best." Leslie Page Moch, Michigan State University